Prologue: Legal regime of working time: a doctrinal study in tribute to Professor Juan García Blasco, through his personal and scientific profile: Monograph on labor law: on working time and its legal framework - Nicolás-Bernad, José Alberto (Acciones e Investigaciones Sociales, 2023)
Introductory chapter to the figure of someone who has been a teacher of the legal regime of working time at the University of Zaragoza, for many years: Professor García Blasco as Professor of Labor Law at the University of Zaragoza.